Oxidative stress in oocyte aging and female reproduction - Wang, Ling; Tang, Jinhua; Wang, Lei; Tan, Feng; Song, Huibin; Zhou, Jiawei; Li, Fenge (Journal of cellular physiology, 2021)
In a healthy body, reactive oxygen species (ROS) and antioxidants remain balanced. When the balance is broken toward an overabundance of ROS, oxidative stress appears and may lead to oocyte aging. Oocyte aging is mainly reflected as the gradual decrease of oocyte quantity and quality. Here, we aim to review the relationship between oxidative stress and oocyte aging. First, we introduced that the defective mitochondria, the age‐related ovarian aging, the repeated ovulation, and the high‐oxygen environment were the ovarian sources of ROS in vivo and in vitro. And we also introduced other sources of ROS accumulation in ovaries, such as overweight and unhealthy lifestyles. Then, we figured that oxidative stress may act as the “initiator” for oocyte aging and reproductive pathology, which specifically causes follicular abnormally atresia, abnormal meiosis, lower fertilization rate, delayed embryonic development, and reproductive disease, including polycystic ovary syndrome and ovary endometriosis cyst. Finally, we discussed current strategies for delaying oocyte aging. We introduced three autophagy antioxidant pathways like Beclin‐VPS34‐Atg14, adenosine 5‘‐monophosphate (AMP)‐activated protein kinase/mammalian target of rapamycin (AMPK/mTOR), and p62‐Keap1‐Nrf2. And we also describe the different antioxidants used to combat oocyte aging. In addition, the hypoxic (5% O2) culture environment for oocytes avoiding oxidative stress in vitro. So, this review not only contribute to our general understanding of oxidative stress and oocyte aging but also lay the foundations for the therapies to treat premature ovarian failure and oocyte aging in women. This review not only contribute to our general understanding of oxidative stress and oocyte aging but also lay the foundations for the therapies to treat premature ovarian failure and oocyte aging in women.